PENGARUH PENGGUNAAN CHATGPT TERHADAP OPTIMALISASI PENULISAN TUGAS AKHIR MAHASIWA PPKN UNIVERSITAS LAMPUNG - Bagus putra Setiawan; Yunisca Nurmalisa; Nurhayati Nurhayati; Ana Mentari; Fitra Endi Fernanda (STKIP Subang, 2026)
The development of artificial intelligence technology, particularly ChatGPT, has created new opportunities to support students’ academic writing processes. However, completing a final thesis remains challenging due to limited scientific writing skills, difficulties in finding references, and low levels of efficiency, effectiveness, and writing quality. The utilization of ChatGPT is considered an alternative solution to assist students in overcoming these obstacles, enabling a more optimal thesis-writing process. This study aims to determine the level of ChatGPT usage, analyze the optimization of final thesis writing, and examine the effect of ChatGPT usage on the optimization of thesis writing among students of the Pancasila and Civic Education Study Program, University of Lampung, Class of 2022. This research employed a quantitative approach using a survey method, involving 64 students as respondents. Primary data were collected through questionnaires and analyzed using simple linear regression with the assistance of SPSS version 26. The results indicate that the use of ChatGPT is categorized as high in terms of usage intensity and skills, while the optimization of thesis writing is also classified as high in terms of efficiency, effectiveness, and quality. Statistically, ChatGPT usage has a significant effect on the optimization of thesis writing, with a significance value of 0.000 < 0.05. Therefore, ChatGPT plays a positive role in improving the speed, accuracy, and quality of thesis writing, while still requiring critical thinking and academic ethics to maintain the originality of scientific work.